Etat des connaissances sur le saumon en France - Dumas, J; Prouzet, P; Porcher, J.p.; Davaine, P (Publ. CNEXO (France) (Actes Colloq.)(no. 12), 1979)
At present, there are no more than 30 salmon rivers in France located mainly in Brittany, lower Normandy, Loire-Allier basin and Adour-Gave Basin. The depletion of salmon populations has been general and more pronounced for the last years (less thant 5.000 fish captured per year since 1973). The main causes of this depletion are : dams without fish ways, new causes of variation of flow, pollutions, overfishing either in rivers or in the sea (Greenlandsea). In France, Atlantic salmon have a short fresh water life span (mainly 1 or 2 years old smolts). They grow very fast (16 to 18 cm at 1 year and 20-22 cm at two years) and they migrate to the sea mainly in April. The majority of the exploited population spends 2 years or more in the sea, and runs in winter or spring. The stock of grilses turning mainly in summer out of the angling season is underestimated. Precise observations have been gathered on two types of actions : improvement of the environment and restocking.